Pengaruh Kualitas Jasa Perspektif Islam Terhadap Kepuasan dan Loyalitas Pelanggan Hotel Grand Kalimas di Surabaya - Salma, Fitria Solahika (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This study intends to know the influences of service quality perspective Islamic on the satisfication and the customer loyalty of Grand Hotel Kalimas in Surabaya. In achieving the aim, this study uses quantitative approach particularly in path analysis. Questioner is used in this study as primary data source of this study, moreover the data sampling of this study taken from 30 respondents. Meanwhile, method of data collection uses probability sampling with accidental sampling approach.For the results, the writer finds that the quality of perspective Islamic gives significant impact toward the satisfication of the customer, but it does not give significant impact toward the loyalty of customer. However, the satisfication of the customer gives significant influence toward the loyalty of the customer, Islamic perspective of service quality indirect effect on customer loyalty.